2014
DOI: 10.1182/blood.v124.21.398.398
|View full text |Cite
|
Sign up to set email alerts
|

ABL001, a Potent Allosteric Inhibitor of BCR-ABL, Prevents Emergence of Resistant Disease When Administered in Combination with Nilotinib in an in Vivo Murine Model of Chronic Myeloid Leukemia

Abstract: Background: Chronic myelogenous leukemia (CML) and a subset of acute lymphoblastic leukemia (ALL) are caused by the t(9;22)(q34;q11.2) chromosome translocation, resulting in fusion of the BCR and ABL1 genes on the Philadelphia chromosome to encode constitutively active ABL1 kinase. Despite the dramatic progress made over the past decade with tyrosine kinase inhibitors (TKIs) in the treatment of CML, allogeneic stem cell transplant is considered the only proven curative therapy. To achieve cure or benefit from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Preclinical modeling in Ba/F3 cells [ 23 , 29 ] indicates that asciminib is transported by ABCB1, however, we now show that asciminib is also transported by ABCG2. Asciminib-mediated cell death was evaluated in K562-Dox (ABCB1 overexpressing) and K562-ABCG2 overexpressing cells compared with parental K562 cells (negligible ABCB1 and ABCG2 expression).…”
Section: Resultsmentioning
confidence: 45%
See 1 more Smart Citation
“…Preclinical modeling in Ba/F3 cells [ 23 , 29 ] indicates that asciminib is transported by ABCB1, however, we now show that asciminib is also transported by ABCG2. Asciminib-mediated cell death was evaluated in K562-Dox (ABCB1 overexpressing) and K562-ABCG2 overexpressing cells compared with parental K562 cells (negligible ABCB1 and ABCG2 expression).…”
Section: Resultsmentioning
confidence: 45%
“…Native c-Abl1 contains a myristate moiety that functions as an auto regulator; however, the myristate group is lost upon fusion to Bcr causing the constitutive activation associated with Bcr-Abl [ 20 , 21 ]. Asciminib and other allosteric inhibitors mimic the myristate group locking Bcr-Abl in an inactive conformation and inhibiting kinase activity [ 22 , 23 ]. Following preclinical modelling, which demonstrated both sustained elimination of tumors in a mouse model of leukemia (when used in combination with nilotinib) and activity against clinically relevant kinase domain mutations in vitro [ 23 ], asciminib entered open label phase I clinical trial for patients with refractory CML or Ph+ ALL ( http://clinicaltrials.gov/show/NCT02081378 ) alone and in combination with imatinib or nilotinb or dasatinib.…”
Section: Introductionmentioning
confidence: 99%
“…5 The KCL-22 cell line is a blast crisis (CML-BC) Ph+ cell line with no BCR-ABL mutations. 5 In a KCL-22 murine subcutaneous xenograft model, when asciminib was administered as a single agent, tumor regression was observed at doses of 7.5 mg/kg twice daily and above. Efficacy in the KCL-22 xenograft model correlated with the complete inhibition of the downstream pharmacodynamic (PD) marker STAT5.…”
mentioning
confidence: 99%
“…6 Asciminib displays potent antitumor activity in vivo, with a clear pharmacokinetic (PK)/PD/efficacy relationship. 5 Recent phase 1 clinical trials on asciminib in patients with CML and Ph+ ALL have shown that in patients intolerant or resistant to at least 2 TKIs, a majority of the patients achieved major molecular response after 12 months of treatment. 7 Based on the results from a first-in-human study, the 40-mg twice-daily dose of asciminib was declared the recommended dose in patients with chronic myeloid leukemia in chronic phase (CML-CP) without T315I mutations.…”
mentioning
confidence: 99%
“…ABL001 binds to the myristoyl pocket of ABL1 kinase leading to a formation of an inactive kinase conformation 84 . Recent studies have shown that treatment with ABL001 combined with ATP-competitive inhibitors can help prevent resistance in chronic myeloid leukemia 85,86 .…”
Section: Allosteric Inhibitors -Third Generationmentioning
confidence: 99%